Freedom Choices: How Black Mothers Living in Jim Crow Protected Their Children from Anti-Black Racism and Prepared Them for Success - LaShawnDa Pittman; Alana Lim; Ayan Mohamed; Mia Schuman; Rachel Vulk; Rina Yan (Genealogy)
In this article, we examine how Black mothers devised strategies of resistance to prepare and protect their children during the Jim Crow era. Grounded in Black feminist standpoint theory, we rely on Black women’s own perspectives to understand how interlocking systems of oppression shaped their mothering experiences and practices. We use Dedoose cloud-based software to conduct a content analysis of 210 oral histories from two oral history repositories. Our grounded theory approach to data analysis entailed a multistage coding process, revealing that Black mothers strategized to provide their children choices in the present that would give them more freedom and opportunities in the future. We refer to this mothering practice as the cultivation of “freedom choices”. Freedom choices seek to minimize the hindrances and restraints that shape the choices available to Black children and to expand their available options. Black mothers fostered freedom choices by relying on both informal and formal education. They used informal education to teach their children restraint, resistance, and when to deploy which, and how to negotiate space. Black mothers facilitated their children’s educational pursuits in the face of structural barriers by (1) leveraging their own sweat equity, (2) tapping into their mutual aid networks, (3) challenging landowners, and (4) insisting on prioritizing their children’s education even when their partners did not.